New and revised cyrtospiriferid (Spiriferida) brachiopods from the lower Famennian (Upper Devonian) of Armenia. (July 2022) - Serobyan, Vahram; Danelian, Taniel; Crônier, Catherine; Grigoryan, Araik; Mottequin, Bernard
Abstract: The Upper Devonian sedimentary sequences of Central Armenia, which mainly consist of shallow water, mixed carbonate-siliciclastic deposits, contain abundant and diverse brachiopods that are dominated by spiriferides. Based on newly collected material from the lower Famennian Aramazdospirifer orbelianus brachiopod zone (coeval to the Palmatolepis crepida conodont zone) of Armenia, we here introduce two new cyrtospiriferid genera and fully document their type species, including their intraspecific variability. Pentagonospirifer n. gen. is a monospecific genus assigned to the subfamily Cyrtospiriferinae that is currently known only from the lower Famennian of Armenia; it is likely that its type species, P . abrahamyanae n. sp., evolved from the species Cyrtospirifer verneuili sensu Abrahamyan, known from the Frasnian and lower Famennian of Armenia. The second new genus, Tornatospirifer n. gen., is assigned to the subfamily Cyrtiopsinae and defined on the basis of one of the most biostratigraphically valuable cyrtospiriferid species, namely T . armenicus n. comb., described previously from the lower Famennian Aramazdospirifer orbelianus Zone of Armenia. It is likely that it evolved from a Frasnian ancestral stock of Tiocyrspis Sartenaer, known from northwestern Europe, which probably migrated during the early Frasnian to the north Gondwanan margin. A neotype is selected for Abrahamyan's species because the type material is lost. Epibionts ( Cornulites, Hederella ) attached to brachiopods are also documented for the first time from the Upper Devonian of Armenia. UUID: http://zoobank.org/923d232f-cd6a-48bb-8a05-27c689058b65 .